Digital Ads Sdn Bhd / Muhammad Raqwan Che Ramli - Che Ramli, Muhammad Raqwan (Faculty of Business and Management, 2025)
My internship journey began on 12 August 2024 at Digital Ads Sdn Bhd in Kuala Lumpur and lasted for six months, ending on 24 January 2025. During this time, I worked as a TikTok Marketing Content Creator Intern, a role that not only matched my interests but also fulfilled the requirements of my academic program. My responsibilities included creating engaging TikTok content, managing multiple accounts, and collaborating with affiliates, all of which gave me valuable hands-on experience in the fast-paced digital marketing industry. This report shares insights I gained during my internship, based on my experiences, discussions with colleagues, guidance from my supervisor, and research. It starts with an introduction to the company and its culture, followed by an overview of the services they offer and a reflection on my training. The report also includes a SWOT analysis of Digital Ads Sdn Bhd, focusing on strengths, challenges, and opportunities I observed. One key challenge I noticed was the issue of employee shortages, particularly in the TikTok Marketing Department. This analysis, supported by my observations and discussions, serves as the foundation for recommendations to address these challenges and improve the company’s efficiency. This internship was an incredible learning experience. It allowed me to apply what I’ve learned in my studies to real-world scenarios, develop creative and problem-solving skills, and deepen my understanding of digital marketing. The report concludes with my recommendations and a reflection on how this journey has helped me grow personally and professionally.